ANALISIS KINERJA KEUANGAN PADA KOPERASI TIRTA DHARMA PERUSAHAAN DAERAH AIR MINUM KOTA PEKANBARU - Risky Saputra; La Ode Syarfan (UIR Press, 2017)
He financial performance of the company is a description of the financial condition of a company that is analyzed with the tools of financial analysis, so it can be known about either the bad financial condition of a company that reflects the performance of work in a certain period. A good financial performance can be judged from the results of an analysis that gets a percentage that conforms to a predetermined standard. The guidelines used in measuring the financial performance of this cooperative use the standards of the Ministerial Decree of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia No. 96 / Kep / M.KUKM / IX / 2004 on Guidelines on Operational Standard Management of Savings and Loans Cooperatives and Savings and Loans Unit. The location of this research is located in Cooperative Tirta Dharma Municipal Water Company Pekanbaru street Jend. Sudirman No 246 Tangkerang Pekanbaru. The method of data analysis used is Descriptive Quantitative Method Percentage, that is by explaining the data that already exist then processed and produce results in the form percentage.Ratio analysis used in measuring Financial Performance at Tirta Dharma Cooperative Municipal Water Company Pekanbaru using Ratio Analysis of Liquidity, Solvability and Profitability. Overall Ratio Analysis performed to produce a good ratio Ratio. Although some are included in the Less Good Criteria.The conclusion that can be obtained from the above analysis and discussion is that the overall ratio analyzed has produced a fairly good ratio and has been in accordance with predefined standards. Things that need to be improved that should cooperative Tirta Dharma do Ratio Analysis in the next year.